3D bioprinting in airway reconstructive surgery: A pilot study. (October 2022) - Torsello, Miriam; Salvati, Antonio; Borro, Luca; Meucci, Duino; Tropiano, Maria Luisa; Cialente, Fabrizio; Secinaro, Aurelio; Del Fattore, Andrea; Emiliana, Caristo Maria; Francalanci, Paola; Battafarano, Giulia; Cacciotti, Ilaria; et al.
Abstract: Objectives: Open surgery is a reliable choice for congenital subglottic stenosis, that represents the third most common congenital anomaly of the larynx. One of the procedures performed is anterior laryngotracheal reconstruction (LTR) with anterior rib graft. The objective of this preliminary study was to evaluate the potential of 3D printing technology for the realization of laryngo-tracheal scaffold in Polycaprolactone (PCL) implanted in vivo in ovine animal model. Methods: A 3D computer model of a laryngeal graft and a tracheal graft was designed and printed with PCL through 3D additive manufacturing technology. The scaffolds were seeded with autologous mesenchymal stem cells and cultured in vitro for up to 14 days. Anterior graft LTR with 3D printed scaffolds was performed on 5 sheep. The animals underwent endoscopic examinations at the first, 3rd, 6th, and 12th weeks after surgery and before sacrifice. The integration of the material was evaluated by the pathologist. Results: Two animals showed a favourable postoperative course and were sacrificed at 6 months postoperatively. In these cases, we observed endoscopically a complete integration of the cellularized PCL scaffold into the peri-implant tissues, and the pathologist found the growth of respiratory epithelium on the scaffold's inner surface. Other two animals showed a difficult post-operative recovery characterized by respiratory distress resulting in early sacrifice on postoperative days 31 and 33. In these animals we found a poor integration of the grafts into the tracheal structure, and a better integration of the laryngeal scaffold. The last animal developed a wound abscess and was sacrificed 80 days after surgery. We observed, in this case, a poor scaffold integration and an acute inflammatory reaction. Conclusions: From the preliminary data obtained we found that the excessive stiffness of the material, along with the anatomical features of the sheep, is a major limitation of this study. It will be necessary in the future to create a new biocompatible, more flexible and elastic graft, to achieve greater integration into surrounding tissues. Bioconstructed grafts could simplify surgery for the treatment of laryngo-tracheal stenosis, particularly in the treatment of long tracheal stenoses, which have, at the moment, very complex surgical options. Level of evidence: NA.